Pertimbangan Hakim Dalam Isbat Nikah Di Pengadilan Agama Curup Ditinjau Dari Upaya Pembentukan Keluarga Sakinah - Juliando, Reno (UIN Fatmawati Sukarno Bengkulu, 2016)
Consideration Of The Judge On Isbat Nikah In Religious Court Of Curup Viewed From The Effort Of Establishing Harmonious Family. Marriage is one of the instinctive needs of man. To ensure the sanctity and holiness of marriage is maintained, then the state is in this case the government took over to set it up in order to achieve the purpose of marriage is essential to the necessity of recording the wedding on the authorities. But the fact in the community turned out there were people who did not record the wedding and marriage to the authorities. To resolve these problems, the state set by specifying the possibility of isbat nikah application efforts through the Religious Courts. This research is a field research in the form of case studies, using qualitative method, through a normative juridical approach. The results showed that in the case isbat nikah, a lot of consideration of the judge who did not institute the legal basis regulating this matter which is a compilation of Islamic law article 7, so a lot of determination or decision in isbat wedlock is not appropriate because it does not contain elements of fairness / philosophical certainty legal / normative or juridical and benefits / sociological. Consequently, there is underestimation on the institution of marriage by not registering the marriage, lax morality of premarital promiscuity, and leads to the difficulties materialize harmonious family.